The Wiley handbook of cognitive control - Egner, Tobias (Oxford Wiley-Blackwell, 2017)
Covering basic theory, new research, and intersections with adjacent fields, this is the first comprehensive reference work on cognitive control ? our ability to use internal goals to guide thought and behavior. Draws together expert perspectives from a range of disciplines, including cognitive psychology, neuropsychology, neuroscience, cognitive science, and neurology Covers behavioral phenomena of cognitive control, neuroanatomical and computational models of frontal lobe function, and the interface between cognitive control and other mental processes Explores the ways in which cognitive control research can inform and enhance our understanding of brain development and neurological and psychiatric conditions
Keywords: Inteligencia; Libros electrónicos